Instilling values and ethics in higher education institutions. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2014)
Values and ethics are two concepts that are inter-related. Halstead and Taylor (in Zegward & Campbell, 2011, p. 3), define values as “principles, fundamental convictions, ideals, standard of life stances which act as general guide to behaviour, or as a reference point in decision making, or evaluation of beliefs, or actions”. In contrast, ethics are righteous conducts which adhere to a values-based judgment system (Garg, 2013). Buckeridge (2002, in Zegward & Paul, 2011, p. 4) defines ethics as the “application or outcomes of adherence to such value systems”.